Technological innovation in dairy herd data management: Applications - Bertipaglia, Liandra Maria Abaker; Melo, Gabriel Maurício Peruca de; Melo, Wanderley José de; Santos, Cleverson Oliveira dos; Pereira, Luis Arthur Malta; Orlandi, Cássia Maria Barroso; Alexandre , Jéssica Weschenfelder; Alves, Thiago de Oliveira; Dian, Paulo Henrique Moura (Seven Editora, 2024)
Family enterprises have as their main characteristic the management by their own family and in them, the family works directly, with or without the help of others. It can be said that family farming represents a social innovation and that, regardless of the size of the enterprise, it must be managed to remain sustainable. With this in mind, this chapter deals with a study that aimed to program a software for the technical and economic management of the dairy production system of family farms, so that their managers will have data for decision-making in the rural business, as well as the professionals of the rural extension can provide rural assistance. The first step of the research was based on the identification and characterization of the evolutionary profile of small family farms, to identifying the technical demands of dairy farming on these family farms. The second step was the development of the computerized app, which used open-source PHP (Hypertext Preprocessor) programming language and was stored on the internet. The application can be accessed at http://www.pmppa.com.br/gestor/, running on the Window platform. The final step was the application test with the researched family farm properties data. The computerized app consists of easy data entry and handling, accessed online, with tools for zootechnical control (nutritional, reproductive and sanitary management) and management (production cost). The result was a free computerized app that generates and provides information in a simple and practical way, providing the family farmer with resources for simple and complex decision making. The application was registered at INPI through the number 512018051699-8. DOI:https://doi.org/10.56238/sevened2023.006-156